An evaluation of seven pioneer corn hybrids for silage and a comparison of irrigated vs dryland silages - Tiemann, D.G.; Bolsen, K.K.; Suazo, R.; Johnson, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seven Pioneer corn hybrids and one grain sorghum hybrid were grown under both irrigated and dryland conditions in 1988 and compared for agronomic and silage quality traits. Com hybrid silage yields ranged from 4.5 to 7.6 tons of dry matter (OM) per acre (mean, 5.8 tons) and grain yield, from 64 to 115 bu per acre (mean, 87 bu). Pre-ensiled DM content of the corn hybrids ranged from 26.7 to 33.0% (mean, 29.5%) and plant height from 82 to 108 in. (mean, 94 in.). In a digestion trial with sheep, apparent DM digestibility ranged from 66.0 to 71.0% (mean 69.6%); voluntary intake from 1,104 to 1,220 g of DM per d (mean 1,163 g); and digestible DM intake from 754 to 862 g per d (mean 810 g). The ranges all contained significant differences, indicating that corn hybrid selection will likely influence agronomic and silage quality traits and subsequent animal performance per acre. Agronomic performance and nutritive value of the irrigated and dryland grain sorghums were similar. However, both grain sorghums had superior silage and grain yields compared to the dryland corns.
Keywords: Beef; Corn; Hybrid; Silage; Irrigated; Dryland